UJI FITOKIMIA DAN ANTIBAKTERI EKSTRAK ETANOL BIJI MAHONI (Swietenia mahagoni (L.) Jacq) - Arwidhiah, Nanda; Saleh, Chairul; Astuti, Winni (Jurusan Kimia FMIPA UNMUL, 2021)
Phytochemical test and antibacterial activity of ethanol extract of Mahoni seed (Swietenia mahagoni (L.) Jacq) have been done. The extraction of Mahoni seed samples was carried out by the maceration method using ethanol as a solvent. An antibacterial activity test was carried out using the agar diffusion method. Phytochemical tests results show that ethanol extract of Mahoni seeds has secondary metabolites of alkaloid, triterpenoid, and phenolic compounds. The antibacterial activity test results obtained MIC values for Streptococcus mutans bacteria were 1.25-2.5% and for Salmonella typhi bacteria at 0.625-1.25%. Ethanol extract of Mahoni seeds has broad-spectrum antibacterial activity.